Kajian Komunikasi Massa Menurut Perspektif Tradisi - Mulyanti Syas (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2012)
The conceptualization of mass communication are often associated with its massive, heterogeneous, delayed feedback, and so on. This concept became confused after the emergence of a variety of communications media with more advanced techniques such as computers, the Internet and handpone with various forms of convergence. The discovery of this new communication technology makes demassifikasi as one of the properties of mass communication, in contrast with the initial concept of mass communication. Seeing this, Turow suggests replaced with the term mass media. Chaffe and Metzger developed the concept of mass communication by evaluating three critical conceptualization of the mass communication, namely: 1) the mass communication media as an institution 2) Mass communication as a social problem, and 3) mass communication as an academic study